LBA1Brigatinib vs crizotinib in patients with ALK inhibitor-naive advanced ALK+ NSCLC: Updated results from the phase III ALTA-1L trial. (24th November 2019) - Camidge, R; Kim, H R; Ahn, M-J; Yang, J C-H; Han, J-Y; Hochmair, M J; Lee, K H; Delmonte, A; Garcia Campelo, M R; Kim, D-W; Griesinger, F; Felip, E; et al.
Abstract: Background: In the first preplanned interim analysis (IA) from ALTA-1L (NCT02737501; median follow-up BRG/CRZ: 11.0/9.3 mo, 99 PFS events), BRG demonstrated superior BIRC-assessed PFS and improved patient-reported quality of life vs CRZ. We report results of the second IA planned at 75% of 198 expected events. Methods: Patients (pts) with ALK inhibitor–naive advanced ALK+ NSCLC and ECOG PS 0–2 were enrolled. One prior chemotherapy for advanced NSCLC was allowed. Asymptomatic CNS metastases were allowed. Pts were stratified by baseline (BL) brain metastases and prior chemotherapy. All pts had brain MRI at each tumor assessment. Pts were randomized 1:1 to BRG 180 mg QD (with 7-day lead-in at 90 mg) or CRZ 250 mg BID. Pts in the CRZ arm were offered BRG at progression. Primary endpoint: BIRC-assessed PFS (RECIST v1.1). Secondary endpoints included confirmed ORR, confirmed iORR, iPFS by BIRC, OS, and safety. Results: 275 pts were randomized (BRG/CRZ, n = 137/138); median age 58/60 y. 26%/27% received prior chemotherapy; 29%/30% had BL brain metastases. As of 28 Jun 2019, median follow-up was BRG/CRZ: 24.9/15.2 mo, with 150 PFS events. HR of BIRC-assessed PFS was 0.49 (95% CI 0.35–0.68, log-rank P < 0.0001); BRG mPFS was 24.0 mo (95% CI 18.5–NE) vs CRZ 11.0 mo (95% CI 9.2–12.9). Investigator-assessed PFS HR was 0.43 (95% CI 0.31–0.61, median 29.4 vs 9.2 mo). OS was immature (total events: 33/37, BRG/CRZ). In pts with BL brain metastases, the PFS HR was 0.25. Data were less mature in pts without BL brain metastases treated with BRG. Table shows additional efficacy data. Most common TEAEs grade ≥3: BRG: increased CPK (24.3%) and lipase (14.0%), hypertension (11.8%); CRZ: increased ALT (10.2%), AST (6.6%), and lipase (6.6%). Any grade ILD/pneumonitis (BRG/CRZ): 5.1%/2.2%; discontinuations due to AE (BRG/CRZ): 12.5%/8.8%. Conclusions: BRG showed durable PFS superiority vs CRZ in ALK inhibitor–naive ALK+ NSCLC. Clinical trial identification: NCT02737501. Editorial acknowledgement: Peloton Advantage, LLC, an OPEN Health company, Parsippany, NJ, USA, and funded by Millennium Pharmaceuticals, Inc., a wholly owned subsidiary of Takeda Pharmaceutical Company Limited, Cambridge, MA, USA. Legal entity responsible for the study: ARIAD Pharmaceuticals, Inc., a wholly owned subsidiary of Takeda Pharmaceutical Company Limited. Funding: ARIAD Pharmaceuticals, Inc., a wholly owned subsidiary of Takeda Pharmaceutical Company Limited. Disclosure: R. Camidge: Honoraria (self): AstraZeneca; Honoraria (self), Research grant / Funding (self): Takeda; Honoraria (self): Arrys/Kyn; Honoraria (self): Novartis; Honoraria (self): Celgene; Honoraria (self): Clovis; Honoraria (self): Orion; Honoraria (self): Revolution Med; Honoraria (self): Lycera; Honoraria (self): Bio-Thera DSMB; Honoraria (self): Hansoh SRC; Honoraria (self): Daichi Sankyo; Honoraria (self): Ignyta; Honoraria (self): Roche/Genentech; Honoraria (self): Mersana Therapeutics; Honoraria (self): G1 Therapeutics; Honoraria (self): Genoptix. H.R. Kim: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim. M. Ahn: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: BMS; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self), Advisory / Consultancy: Novartis. J.C. Yang: Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy: Eli Lilly; Honoraria (self), Advisory / Consultancy: Bayer; Honoraria (self), Advisory / Consultancy: Roche/Genentech/Chugai; Honoraria (self), Advisory / Consultancy: Astellas; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self), Advisory / Consultancy: Merck Serono; Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self), Advisory / Consultancy: Novartis; Honoraria (self), Advisory / Consultancy: Celgene; Honoraria (self), Advisory / Consultancy: Merrimack; Honoraria (self), Advisory / Consultancy: Yuhan Pharmaceuticals; Honoraria (self), Advisory / Consultancy: BMS; Honoraria (self), Advisory / Consultancy: Ono Pharmaceutical; Honoraria (self), Advisory / Consultancy: Daiichi Sankyo; Honoraria (self), Advisory / Consultancy: Takeda; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Hansoh Pharmaceuticals. J. Han: Research grant / Funding (self): Roche. M.J. Hochmair: Honoraria (self): AstraZeneca; Honoraria (self): Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy: Merck Sharp & Dohme; Honoraria (self): Pfizer; Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: Takeda; Advisory / Consultancy: Novartis. K.H. Lee: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Eli Lilly; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim. A. Delmonte: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Boehringer Ingelheim. M.R. Garcia Campelo: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Ariad; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: BMS; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Boehringer Ingelheim. F. Griesinger: Advisory / Consultancy: Ariad; Advisory / Consultancy: Takeda; Advisory / Consultancy: Roche; Advisory / Consultancy: Novartis; Advisory / Consultancy: Pfizer. E. Felip: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: BMS; Advisory / Consultancy: Celgene; Advisory / Consultancy: Eli Lilly; Advisory / Consultancy: Guardant Health; Advisory / Consultancy: MSD; Advisory / Consultancy: Novartis; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Roche; Advisory / Consultancy: Takeda; Advisory / Consultancy: Merck. R. Califano: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: BMS; Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy: Takeda; Honoraria (self), Advisory / Consultancy: Novartis. A. Spira: Advisory / Consultancy: Ariad; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Clovis Oncology; Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche. S. Gettinger: Advisory / Consultancy, Research grant / Funding (self): Ariad; Advisory / Consultancy, Research grant / Funding (self): BMS; Advisory / Consultancy: Janssen; Research grant / Funding (self): AstraZeneca/MedImmune; Research grant / Funding (self): Boehringer Ingelheim; Research grant / Funding (self): Incyte; Research grant / Funding (self): Pfizer; Research grant / Funding (self): Roche/Genentech. M. Tiseo: Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Advisory / Consultancy, Speaker Bureau / Expert testimony: BMS; Advisory / Consultancy, Speaker Bureau / Expert testimony: Boehringer Ingelheim; Advisory / Consultancy, Speaker Bureau / Expert testimony: Eli Lilly; Advisory / Consultancy, Speaker Bureau / Expert testimony: MSD; Advisory / Consultancy, Speaker Bureau / Expert testimony: Novartis; Advisory / Consultancy, Speaker Bureau / Expert testimony: Otsuka; Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Pierre Fabre; Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche. Q. Ni: Full / Part-time employment: Takeda. P. Zhang: Full / Part-time employment: Takeda. S. Popat: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Boehringer Ingelheim; Research grant / Funding (institution): Epizyme; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: BMS; Research grant / Funding (institution): Clovis Oncology; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Roche; Research grant / Funding (institution): Lilly; Honoraria (self), Research grant / Funding (institution): Takeda; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self): Chugai Pharma; Advisory / Consultancy: Novartis; Advisory / Consultancy: Pfizer; Advisory / Consultancy, Travel / Accommodation / Expenses: MSD; Advisory / Consultancy: Guardant Health; Advisory / Consultancy: AbbVie.